Leucas aspera: A review - Prajapati, M. S.; Patel, J. B.; Modi, K.; Shah, M. B. (Pharmacognosy Reviews, 2010)
Leucas aspera commonly known as ‘Thumbai’ is distributed throughout India from the Himalayas down to Ceylon. The plant is used traditionally as an antipyretic and insecticide. Medicinally, it has been proven to possess various pharmacological activities like antifungal, antioxidant, antimicrobial, antinociceptive and cytotoxic activity. Further, studies reveal the presence of various phytochemical constituents mainly triterpenoids, oleanolic acid, ursolic acid and β-sitosterol, nicotine, sterols, glucoside, diterpenes, phenolic compounds (4-(24-hydroxy-1-oxo-5-n-propyltetracosanyl)-phenol). These studies reveal that L. aspera is a source of medicinally active compounds and have various pharmacological effects; hence, this drug encourage fi nding its new therapeutic uses.
Keywords: Antimicrobial activity; lamiaceae; Leucas aspera; triterpenoid